Parasite Prevalence Oodinium sp. in Cantang Hybrid Grouper Cultivated in Recirculating Aquaculture System - Widiartini, Kadek Leni; Antara, Kadek Lila; Mahardika, Ketut; Setiabudi, Gede Iwan (Advances in Tropical Biodiversity and Environmental Sciences, 2022)
The aims of this study were to determine clinical symptoms, mortality, prevalence, and histopathology of Cantang hybrid grouper fish infected with Oodinium sp. on the Cantang. The study was conducted by direct observation of clinical symptoms, calculating the number of fish mortality, and measuring the quality of water in the tank using the Cantang. While histopathology was conducted in the laboratory using 10 samples of sick fish with an average total length of 10.6 ± 0.69 cm and a weight of 18.6 ± 1.77 g. The results showed that the fish seen swimming weakly on the surface of the water near aeration or standing still at the bottom of the tub, decreased appetite, had pale or darker body color, and were thin. Observation of skin and gill mucus under a microscope showed the presence of ectoparasites Oodinium sp. in massive quantities in almost every gill sheet. The mortality of fish infected with Oodinium sp. in the Cantang of 26.84±3.9%, with a prevalence of 49.59%. Histopathologically the gill lamellae of fish infected with Oodinium sp. shows the occurrence of hyperplasia which causes the union of several gill lamellae.